Producción musical del tema "Dame tu Corazón" del artista Renato Ortega - Alomoto Jami, Edwin Xavier (2017)
The present work corresponds to the production of the musical theme “Dame tu corazón” by the artist Renato Ortega, who practices a musical style that fuses the elements of salsa, with the freshness and innovation of pop. It is important to point out that to carry out the recording of this musical theme, a systematic process of pre-production, recording, editing and mixing was carried out, obtaining the first single that will be part of the first album of this artist. In this way to carry out the different stages of recording a collective work was established between the artist Renato Ortega and the producer, as well as with the rest of musicians who participated in the production of the musical theme, which was recorded in the studio Massive Record Music, where all the musical instruments were recorded through the program Protools 10 with a console Avid Venue S3L, that allowed to obtain the desired sound. Also thanks to the different microphone techniques used and the performance of each of the musicians, the corrections made in each instrument were minimal, aspect that proved positive for the recording, since it allowed to add certain sound arrangements that improved the musical theme “Dame Your heart”, “which was produced from the reference theme” Pale Flower by composer Marc Anthony, resulting in a quality product to be promoted nationally.